Programa Institucional de Bolsas de Iniciação à Docência– PIBID: reflexões da prática docente no processo de ensino e aprendizagem nos anos iniciais na Escola Estadual Araújo Filho - Silva, Karoline Guerreiro (Brasil, 2025)
This experience report aims to demonstrate the path that was taken in the field of education during this period as a student at the Federal University of Amazonas (UFAM), in teacher training through this Institutional Program of Teaching Initiation Scholarship (PIBID). PIBID provides the student with an extremely important experience, since it is in the school space that professional identity is constructed by articulating theory and practice, providing new perspectives and reflections on teaching practice and school reality. The Araújo Filho State School where the experience report was carried out, at the beginning of 2023 it was in the 4th grade class with 29 students and from the middle of the year 2023 until the end with the 1st grade class with 23 students. In 2024 we maintained it in the 1st grade class. The type of research selected is field experience report, which is configured in the immersion of a certain group, verifying their relationship within the community, as time was allocated in a field school for the sharing of experiences. The authors of this research are: Day (2001), Canan (2012), Cunha (2010), Imbernón (2012), Mortatti (2019) and Soares (2009). Therefore, it is recommended for future academics who will take the undergraduate course in pedagogy to be innovative teachers in training capable of being transformative agents of education, and that the PIBID program be a primary path to improve skills, didactics and knowledge in the classroom.